2002
DOI: 10.1007/s11745-002-0939-6
|View full text |Cite
|
Sign up to set email alerts
|

Positional distribution of CLA in TAG of lamb tissues

Abstract: The content and positional distribution of CLA in TAG fractions of lamb tissues was examined with either preformed CLA or the linoleic acid precursor of CLA in the diet as experimental treatments. The CLA content of phospholipid (PL) from these tissues was also examined. Thirteen lambs were randomized to the following dietary treatments: (i) control diet (no supplement); (ii) CLA supplementation (0.33 g d(-1) for 21 d prior to weaning) to milk-replacer of pre-ruminating lambs, or (iii) feeding linoleic acid-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…1 and 2 and used for stereospecific analysis to determine if CLA was specifically esterified to a particular position on the glycerol moiety. From the two experiments, there were four muscle samples from steers fed CON, 6% SFO, and 500 IU vitamin E per day, but only two samples from animals fed 3% SFO and 6%SFO with 500 IU vitamin E. The procedure described by Paterson et al (2002) was used for determination of proportion of fatty acids (%) at sn-2 and sn-1/3 position on the TAG. The meat samples were freeze-dried and extracted with ethyl ether to determine total lipid (TL) content.…”
Section: Positional Distribution Of Fatty Acids On Tagmentioning
confidence: 99%
“…1 and 2 and used for stereospecific analysis to determine if CLA was specifically esterified to a particular position on the glycerol moiety. From the two experiments, there were four muscle samples from steers fed CON, 6% SFO, and 500 IU vitamin E per day, but only two samples from animals fed 3% SFO and 6%SFO with 500 IU vitamin E. The procedure described by Paterson et al (2002) was used for determination of proportion of fatty acids (%) at sn-2 and sn-1/3 position on the TAG. The meat samples were freeze-dried and extracted with ethyl ether to determine total lipid (TL) content.…”
Section: Positional Distribution Of Fatty Acids On Tagmentioning
confidence: 99%
“…Chardigny et al [9] studied the location of labelled CLA in TAG at either the sn1/3 or sn2 position, and found that the label was recovered in oxidation products when CLA was in the sn1/3 position but was found in the carcass when the labelled CLA was in the sn2 position. These authors found that dairy CLA was uniformly distributed among the three positions of milk fat, as did Paterson et al [10], who found that bioformed CLA from sheep fed safflower oil aggregated to greater proportions at the sn1/3 position in muscle fat. However, Mir et al [11] found that muscle fat from beef steers fed sunflower oil had greater proportions of CLA at the sn2 position, but the amounts were greater when the dietary oil incorporation level was 3% of diet rather than 6%.…”
Section: Introductionmentioning
confidence: 60%
“…Pancreatic lipase (Lipase from porcine pancreas, Type II; Sigma-Aldrich Canada, Oakville, ON) was used to generate sn2-MAG from TAG [10]. Two milligrams of dried TAG wERE suspended in 500  μ L of pancreatic lipase buffer [1 M Tris-HCl, pH 8, containing 10% gum Arabic (wt/v) and 0.23 M CaCl 2 (wt/v)] by sonication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I). On the contrary, the CLA positional distribution in TAG (sn-2 vs. sn-1/3) of ruminant (lamb) muscle or subcutaneous adipose tissue has been reported to be modified by this dietary factor [17]. Thus, due to its specific rumenic acid distribution within TAG, dairyfat might not be nutritionally equivalent to other ruminant products in terms of rumenic acid availability and activity.…”
Section: Resultsmentioning
confidence: 99%